A Rapid Method for the Detection of Sarcosine Using SPIONs/Au/CS/SOX/NPs for Prostate Cancer Sensing - Uhlirova, Dagmar; Stankova, Martina; Docekalova, Michaela; Hosnedlová, Božena; Kepinska, Marta; Ruttkay-Nedecký, Branislav; Ruzicka, Josef; Fernandez, Carlos; Milnerowicz, Halina; Kizek, Rene (International journal of molecular sciences, 2018)
BACKGROUND: Sarcosine is an amino acid that is formed by methylation of glycine and is present in trace amounts in the body. Increased sarcosine concentrations in blood plasma and urine are manifested in sarcosinemia and in some other diseases such as prostate cancer. For this purpose, sarcosine detection using the nanomedicine approach was proposed. In this study, we have prepared superparamagnetic iron oxide nanoparticles (SPIONs) with different modified surface area. Nanoparticles (NPs) were modified by chitosan (CS), and sarcosine oxidase (SOX). SPIONs without any modification were taken as controls. Methods and Results: The obtained NPs were characterized by physicochemical methods. The size of the NPs determined by the dynamic light scattering method was as follows: SPIONs/Au/NPs (100⁻300 nm), SPIONs/Au/CS/NPs (300⁻700 nm), and SPIONs/Au/CS/SOX/NPs (600⁻1500 nm). The amount of CS deposited on the NP surface was found to be 48 mg/mL for SPIONs/Au/CS/NPs and 39 mg/mL for SPIONs/Au/CS/SOX/NPs, and repeatability varied around 10%. Pseudo-peroxidase activity of NPs was verified using sarcosine, horseradish peroxidase (HRP) and 3,3',5,5'-tetramethylbenzidine (TMB) as a substrate. For TMB, all NPs tested evinced substantial pseudo-peroxidase activity at 650 nm. The concentration of SPIONs/Au/CS/SOX/NPs in the reaction mixture was optimized to 0⁻40 mg/mL. Trinder reaction for sarcosine detection was set up at 510 nm at an optimal reaction temperature of 37 °C and pH 8.0. The course of the reaction was linear for 150 min. The smallest amount of NPs that was able to detect sarcosine was 0.2 mg/well (200 µL of total volume) with the linear dependence y = 0.0011x - 0.0001 and the correlation coefficient r = 0.9992, relative standard deviation (RSD) 6.35%, limit of detection (LOD) 5 µM. The suggested method was further validated for artificial urine analysis (r = 0.99, RSD 21.35%, LOD 18 µM). The calculation between the detected and applied concentrations showed a high correlation coefficient (r = 0.99). NPs were tested for toxicity and no significant growth inhibition was observed in any model system (S. cerevisiae, S. aureus, E. coli). The hemolytic activity of the prepared NPs was similar to that of the phosphate buffered saline (PBS) control. The reaction system was further tested on real urine specimens. Conclusion: The proposed detection system allows the analysis of sarcosine at micromolar concentrations and to monitor changes in its levels as a potential prostate cancer marker. The whole system is suitable for low-cost miniaturization and point-of-care testing technology and diagnostic systems. This system is simple, inexpensive, and convenient for screening tests and telemedicine applications.
Keywords: Prostatic Neoplasms; Limit of Detection; Staphylococcus aureus; nádory prostaty; limita detekce; Chitosan; Humans; zlato; Precision Medicine; Hemolysis; Biomarkers, Tumor; křenová peroxidasa; oxidace-redukce; Sarcosine Oxidase; Escherichia coli; lidé; individualizovaná medicína; sarkosinoxidasa; velikost částic; reprodukovatelnost výsledků; nádorové biomarkery; Ferric Compounds; Horseradish Peroxidase; Male; Reproducibility of Results; Hydrogen-Ion Concentration; železité sloučeniny; Saccharomyces cerevisiae; sarkosin; Oxidation-Reduction; magnetické nanočástice; Gold; mužské pohlaví; koncentrace vodíkových iontů; chitosan; hemolýza; Particle Size; Sarcosine; Magnetite Nanoparticles